Lime-enhanced hydrogen reduction of molybdenite - Mankhand T.R.; Prasad P.M. (My University, 2025)
Kinetics of the direct hydrogen reduction of a high-grade (59 pct Mo) molybdenite (MoS2) concentrate was investigated in the presence of lime as a function of the quantity of lime in the charge, hydrogen flow rate, temperature, and time of reduction. Lime was found to enhance tremendously the reduction rate of MoS2 and drastically reduce H2S emission into the off gas to negligible levels. Successful application of the lime-hydrogen reduction technique was found to depend on the employment of low hydrogen flow rate and moderate temperatures of reduction. In these laboratory studies, best results were obtained with a lime addition ≥ three times the theoretical requirement and at 1173 K in 3.6 ks employing a hydrogen flow rate of 3.33 cm3s-1. The results were tested for the treatment of a low-grade (41 pct Mo) molybdenite concentrate. In this latter case, the procedure consisted of upgrading the concentrate by acid leaching (with dil HC1+HF) followed by lime-hydrogen reduction. The influence of quantity of acids, temperature, and time of leaching were investigated to optimize the conditions required for upgrading the MoS2 concentrate. The molybdenum powders obtained from the highgrade as well as upgraded molybdenite concentrates had 96 to 97 pct purity and could be further refined to 99.9 pct by electron-beam melting. Based on this lime-enhanced hydrogen reduction concept, a new 'Leach-Reduction-Melting' approach has been suggested as an alternative to the traditional methods of molybdenum extraction. © 1982 American Society for Metals and the Metallurgical Society of AIME.